Comorbidity, Pain, Utilization, and Psychosocial Outcomes in Older versus Younger Sickle Cell Adults: The PiSCES Project - Bovbjerg, Viktor E.; Roberts, John D.; Aisiku, Imoigele P.; Levenson, James L.; Smith, Wally R.; McClish, Donna K.; Roseff, Susan D. (BioMed research international, 2017)
Background. Patients with SCD now usually live well into adulthood. Whereas transitions into adulthood are now often studied, little is published about aging beyond the transition period. We therefore studied age-associated SCD differences in utilization, pain, and psychosocial variables. Methods. Subjects were 232 adults in the Pain in Sickle Cell Epidemiology Study (PiSCES). Data included demographics, comorbidity, and psychosocial measures. SCD-related pain and health care utilization were recorded in diaries. We compared 3 age groups: 16–25 (transition), 26–36 (younger adults), and 37–64 (older adults) years. Results. Compared to the 2 adult groups, the transition group reported fewer physical challenges via comorbidities, somatic complaints, and pain frequency, though pain intensity did not differ on crisis or noncrisis pain days. The transition group utilized opioids less often, made fewer ambulatory visits, and had better quality of life, but these differences disappeared after adjusting for pain and comorbidities. However, the transition group reported more use of behavioral coping strategies. Conclusion. We found fewer biological challenges, visits, and better quality of life, in transition-aged versus older adults with SCD, but more behavioral coping. Further study is required to determine whether age-appropriate health care, behavioral, or other interventions could improve age-specific life challenges of patients with SCD.